MARKETING AND UTILIZATION OF MORINGA SEEDS (MORINGA OLEIFERA LAMK) AS WELL WATER PURIFIERS IN PADANG BULAN SELAYANG DISTRICT 2 - Fajriah, Nurul; Sudarmi; Reveny, Julia (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
This service activity was carried out in Padang Bulan Selayang 2 Village, North Sumatra Province. This activity aims to help clear the water from the local dug wells because there are still many dangerous bacteria and metals found in the well water content. To purify well water, it is done by using powdered Moringa oleifera seeds which are put into well water before consumption and Moringa seeds will absorb harmful metals and bacteria contained in the well water content. This service also helps residents of Padang Bulan Selayang 2 Village to be able to make their own Moringa seed powder with tools and materials that are available so that they can meet their daily needs. Marketing can be done from house to house or through an online system by introducing to the general public the benefits of Moringa seeds as well water purifiers.